Operando Stability of Platinum Electrocatalysts in Ammonia Oxidation Reactions - Kim, Haesol; Yang, Woojin; Lee, Woong Hee; Han, Man Ho; Moon, Joonhee; Jeon, Cheolho; Kim, Donghyun; Ji, Sang Gu; Chae, Keun Hwa; Lee, Kug-Seung; Seo, Jiwon; Oh, Hyung-Suk; et al. (AMER CHEMICAL SOC, 2020)
Ammonia has recently received considerable attention as an alternative energy carrier and a carbon-neutral fuel. In this future energy scenario, the ammonia oxidation reaction (AOR) is a pivotal process for onsite hydrogen production and/or electricity generation. However, its implementation is hindered by the nondurable nature of AOR catalysis by platinum. Accordingly, securement of a durable Pt electrocatalysis for the AOR is critical but has been hampered by the well-known chemical deactivation (i.e., poisoning). Additionally, the structural stability, which could also affect durable AOR operation, has scarcely been investigated. Herein, the degradation of Pt catalysts under AOR conditions has been investigated with various operando and in/ex situ spectroscopies. We demonstrate that NH3 (or AOR intermediates/byproducts) modifies the chemical structures of both the Pt surface and dissolved Pt ions, specifically by passivation of the Pt surface with NH3-derived adsorbates and complexation of the dissolved Pt ions, respectively. These modifications lead to a significant acceleration in Pt dissolution but a deceleration in its redeposition, resulting in the augmented structural degradation of Pt catalysts in NH3-containing electrolyte after the Pt has experienced a potential excursion above ca. 1 VRHE. With these understandings, a quasi-stable operation potential window and operational strategy are suggested. The tentative AOR protocol allows prolonged NH3 electrolysis with alleviated Pt dissolution (<0.02 ng cm(Pt)(-2) s(-1)), suggesting that NH3 will be a viable future energy carrier if the rational operational strategy proposed herein is developed further.
Keywords: IN-SITU; ELECTROCHEMICAL OXIDATION; FUEL-CELL; INFRARED-SPECTROSCOPY; DISSOLUTION; MECHANISM; IMPACT; IR; NANOPARTICLES; DEGRADATION